2015
DOI: 10.1002/2013ja019706
|View full text |Cite
|
Sign up to set email alerts
|

An empirical approach to modeling ion production rates in Titan's ionosphere I: Ion production rates on the dayside and globally

Abstract: Titan's ionosphere is created when solar photons, energetic magnetospheric electrons or ions, and cosmic rays ionize the neutral atmosphere. Electron densities generated by current theoretical models are much larger than densities measured by instruments on board the Cassini orbiter. This model density overabundance must result either from overproduction or from insufficient loss of ions. This is the first of two papers that examines ion production rates in Titan's ionosphere, for the dayside and nightside ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
48
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 91 publications
(301 reference statements)
9
48
3
Order By: Relevance
“…Similar model-observation comparisons have previously been performed by Robertson et Figure 4), particularly over the electron energy range 10-60 eV. Among several potential sources of differences (not only directly model related; see Section 3.1), we merely note that Robertson et al (2009) and Richard et al (2015a) used solar flux models in their calculations (based on the solar F 10.7 value), while we in the present work, similar to that done by Lavvas et al (2011), use solar EUV fluxes based on TIMED/SEE measurements. Regarding Lavvas et al (2011), their modeled electron spectra acquired along the T40 flyby agreed reasonably in shape with CAPS/ELS observations for energies <60 eV.…”
Section: Present Work: Suprathermal Electron Intensities In Titan's Isupporting
confidence: 80%
See 4 more Smart Citations
“…Similar model-observation comparisons have previously been performed by Robertson et Figure 4), particularly over the electron energy range 10-60 eV. Among several potential sources of differences (not only directly model related; see Section 3.1), we merely note that Robertson et al (2009) and Richard et al (2015a) used solar flux models in their calculations (based on the solar F 10.7 value), while we in the present work, similar to that done by Lavvas et al (2011), use solar EUV fluxes based on TIMED/SEE measurements. Regarding Lavvas et al (2011), their modeled electron spectra acquired along the T40 flyby agreed reasonably in shape with CAPS/ELS observations for energies <60 eV.…”
Section: Present Work: Suprathermal Electron Intensities In Titan's Isupporting
confidence: 80%
“…It was mentioned in Section 1.4.1 that the modeled electron fluxes by Robertson et al (2009) and Richard et al (2015a) were found to be in good agreement with CAPS/ELS observations. We plan to investigate in detail how the use of different solar EUV flux models affects the calculations of suprathermal electron intensities.…”
Section: Comparisons Of Modeled and Observed Electron Intensitiessupporting
confidence: 70%
See 3 more Smart Citations